Determination of The Level of Paracetamol and Tramadol Hcl Mixture in Tablets by Chemometric Method by Fourier Transform Infrared Spectrophotometry - Gratia Apulina Cindylawsa Purba; Muchlisyam Muchlisyam; Effendy De Lux Putra (Eduvest - Journal of Universal Studies, 2025)
Fixed-dose combinations of paracetamol and tramadol HCl are effective in the treatment of moderate to severe pain. Therefore, the determination of the levels of the mixture of paracetamol and tramadol HCl is very important for the pharmaceutical industry. The purpose of this study was to determine the levels of paracetamol and tramadol HCl mixture using Fourier Transform Infrared combined with partial least square (PLS) chemometric method. This study was conducted by making a calibration model and chemometric validation of each of the five concentrations measured absorbance at specific wave numbers of paracetamol and tramadol HCl. The results of the study on PLS multivariate calibration of paracetamol and tramadol HCl with RMSECV values of 0.06279 and 0.03785, PRESS values of 0.02366 and 0.00860, and R2 values of 0.9995  0.9998, respectively. All validation parameters are within the acceptable range.  This indicates that the method can be used to accurately determine drug levels without separation